Analysis of the Role of Evaluation in Islamic Religious Education Learning at MA Daarul Qur'an - Salwa Salis Himmatul Khoiriyyah Sucarto; Revania Nafi’ah; Siti Nuraeni; Sabiq Faruq Al-Fawwaz; Sofiyana Nadia Fairuz (Penerbit Presisi Pustaka, 2026)
Learning evaluation is a fundamental element in the education system, serving to assess the effectiveness of the learning process. The quality of education can be considered to have good integrity if supported by a systematic, structured, and directed learning system. Various components within educational institutions, such as educators, students, curriculum, facilities and infrastructure, school management, and the educational environment, contribute significantly to improving the quality of learning. Therefore, all these components need to play an active and synergistic role in efforts to develop and improve the learning system on an ongoing basis. This study applies a library research approach as the primary method. The research object is Madrasah Daarul Qur'an Karawang, located in Karawang, West Java. This study aims to analyze and examine in depth the learning evaluation practices implemented in this educational institution.